Saturday

December 20, 2014

December 20, 2014

Posted by **Antia** on Monday, January 23, 2012 at 8:57pm.

a) sin(pi/6)

sin=cos(pi/2 - pi/6)

What do I do next?

- Math -
**Reiny**, Monday, January 23, 2012 at 10:47pmwhat is π/2 - π/6 ??

= 3π/6 - π/6 = 2π/6 = π/3

so sin(π/6) = cos(π/3)

check:

sin(π/6) = sin 30° = 1/2

cos(π/3) = cos 60° = 1/2

All is good!

**Answer this Question**

**Related Questions**

trig - The expression 4 sin x cos x is equivalent to which of the following? (...

Math(Please check) - Use the fundamental identities to simplify the expression. ...

algebra - Can someone please help me do this problem? That would be great! ...

trig - Use the appropriate cofunction to find an equivalent expression for cos ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

Trig! - The identities cos(a-b)=cos(a)cos(b)sin(a)sin(b) and sin(a-b)=sin(a)cos(...

math - Eliminate the parameter (What does that mean?) and write a rectangular ...

Pre Calculus - Use one of the identities cos(t + 2šk) = cos t or sin(t + 2šk) = ...

Pre Calculus - Use one of the identities cos(t + 2šk) = cos t or sin(t + 2šk) = ...

tigonometry - expres the following as sums and differences of sines or cosines ...